2018
DOI: 10.1111/iej.12980
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time dynamic torque values and axial forces during preparation of straight root canals using three different endodontic motors and hand preparation

Abstract: Manual preparation was associated with significantly lower torque peaks compared to rotary instrumentation. The three motors remained well within the safety torque values of the instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Moreover, different electronic motors were used in these studies and it has been reported that actual kinematics values (angles of rotation in reciprocating motion) of some motors differ from manufacturers' declared values (Fidler ) and that intrinsic settings for do not result in consistent kinematics (Bürklein et al ). Thus, another possible explanation for the marked differences might be (unnoticed) deviations from the rotational speed recommended by the manufacturer.…”
Section: Results For the Same Instrument In Different Studiesmentioning
confidence: 99%
“…Moreover, different electronic motors were used in these studies and it has been reported that actual kinematics values (angles of rotation in reciprocating motion) of some motors differ from manufacturers' declared values (Fidler ) and that intrinsic settings for do not result in consistent kinematics (Bürklein et al ). Thus, another possible explanation for the marked differences might be (unnoticed) deviations from the rotational speed recommended by the manufacturer.…”
Section: Results For the Same Instrument In Different Studiesmentioning
confidence: 99%
“…After the resin was set, the teeth were decoronated to a level that kept 15-mm root length to standardize the samples. The periodontal ligament was not simulated in this study in order to investigate pure forces on the internal root canal wall caused by the tested file systems ( 5 ).…”
Section: Methodsmentioning
confidence: 99%
“…The use of rotary file systems was reported to induce less shaping force but more torque than the manual stainless steel files ( 4 , 5 ). Past studies revealed that the force and torque exerted on the tooth during canal shaping directly affected the file fatigue ( 6 - 9 ) as well as the root canal wall ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…They emphasized that rotatory endodontic motors do not provide significant results in clockwise and counterclockwise peaks but manual preparation relatively showed significant peaks as compared to rotatory instruments. 18 Nayak et al 19 acquired the force and vibration signal experienced by endodontic files in the root canal treatment process and predicted the fracture of the self-adjusting file by statistical analysis of force and vibration signals.…”
Section: Introductionmentioning
confidence: 99%